A review of some Neriene spiders (Araneae, Linyphiidae) from China - Li, Jian Yong; Liu, Jie; Chen, Jian (Zootaxa, 2018)
The genus Neriene Blackwall, 1833 from China is reviewed. Two new species are described: Neriene lushanensis n. sp., Neriene orthocera n. sp. Ketambea liupanensis (Tang & Song, 1992) n. comb. and Ketambea nigripectoris (Oi, 1960) n. comb. are transferred from the genus Neriene. Nineteen known species are redescribed or diagnosed and discriminated from related species: Neriene aquilirostralis Chen & Zhu, 1989, Neriene birmanica (Thorell, 1887), Neriene calozonata Chen & Zhu, 1989, Neriene cavaleriei (Schenkel, 1963), Neriene clathrata (Sundevall, 1830), Neriene compta Zhu & Sha, 1986, Neriene decormaculata Chen & Zhu, 1988, Neriene emphana (Walcknear, 1841), Neriene hammeni (Van Helsdingen, 1963), Neriene japonica (Oi, 1960), Neriene limbatinella (Bosenberg & Strand, 1906), Neriene longipedella (Bosenberg & Strand, 1960), Neriene macella (Thorell, 1898), Neriene nitens Chen & Zhu, 1991, Neriene oidedicata (Van Helsdingen, 1969), Neriene poculiforma Liu & Chen, 2010, Neriene radiata (Walckenear, 1841), Neriene strandia (Blauvelt, 1936), and Neriene zhui Chen & Li, 1995.